MICROBIOLOGICAL EXAMINATION OF FRUITS SOLD AT ISI-GATE UMUAHIA, ABIA STATE. - I.U., NWANKWO; MATTHEW, OSARO-; W.O., UCHENDU (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The presence of microorganisms on five fruits (Apple, Banana, water melon, pineapple and pawpaw were examined. Five genera of pathogenic bacteria: (Escherichia coli, Staphylococcus aureus, Bacillus spp, Pseudomonas aeruginosa, Streptococcus spp.) And three fungal genera (Aspergillus spp, Saccharomyces cerevisae and Penicillium spp). were successfully isolated from this study. Water melon carry the highest bacterial load 2.91x103cfu/ml, while the lowest count was observed with Apple 1.10x103cfu/ml, The Total Fungal Count ranged from 1.10x103cfu/ml to 2.63x103cfu/ml. Banana had the higher fungal count: 2.63 x103 cfu/ml while Apple had the lowest count: 1.10 x103 Cfu/ml. The Percentage occurrences of bacteria isolated from the samples revealed both Staphylococcus aureus (100%) and Bacillus spp (100%) to have the highest percentage occurrence while Pseudomonas aeruginosa (40%) had the least percentage occurrence. The percentage occurrence of fungal isolates reveals Saccharomyces spp. (80%) to have the highest percentage occurrence, while Penicillium spp. (40%) had the least percentage occurrence. The presence of these organisms in the fruit juice indicates that their consumption could be hazardous to health. This therefore calls for more hygienic practices in the production of these products.